Tanggung Jawab Pelaku Usaha Pertambangan Rakyat dalam Reklamasi Gumuk Setelah Kegiatan Tambang - Ade Lutfi Prayogo (Lentera Hukum, 2018)
The responsibility in the mining businesses on the post-mining reclamation activities applies to all mining business permits including holders of the People's Mining Permit (IPR). The arrangement of post-mining land reclamation activities for small-scale mining business people on what so-called ‘gumuk’ mining is still not efficient regarding its making and implementation. The legal responsibility of IPR holders in the preparation of planning, implementation, and sanctions depends on regulations made by the regional government. There is a normative gap while there is a lack of guarantee costs for post-mining reclamation due to the absence of mandatory guarantee funds. This is the evidence that there are still many regional governments that have not made regulations on reclamation and post-mining by IPR holders. Therefore, it is necessary to regulate reclamation and post-mining activities for community mining businesses. There is a need to add norms to the implementation rules so that environmental functions can work properly. Keywords: Mining Business, People's Mining Permit, Regional Government